S-Nitrosoglutathione Reductase Plays Opposite Roles in SH-SY5Y Models of Parkinson's Disease and Amyotrophic Lateral Sclerosis. (27th September 2015) - Rizza, Salvatore; Cirotti, Claudia; Montagna, Costanza; Cardaci, Simone; Consales, Claudia; Cozzolino, Mauro; Carrì, Maria Teresa; Cecconi, Francesco; Filomeni, Giuseppe
Abstract : Oxidative and nitrosative stresses have been reported as detrimental phenomena concurring to the onset of several neurodegenerative diseases. Here we reported that the ectopic modulation of the denitrosylating enzyme S -nitrosoglutathione reductase (GSNOR) differently impinges on the phenotype of two SH-SY5Y-based in vitro models of neurodegeneration, namely, Parkinson's disease (PD) and familial amyotrophic lateral sclerosis (fALS). In particular, we provide evidence that GSNOR-knocking down protects SH-SY5Y against PD toxins, while, by contrast, its upregulation is required for G93A-SOD1 expressing cells resistance to NO-releasing drugs. Although completely opposite, both conditions are characterized by Nrf2 localization in the nuclear compartment: in the first case induced by GSNOR silencing, while in the second one underlying the antinitrosative response. Overall, our results demonstrate that GSNOR expression has different effect on neuronal viability in dependence on the stimulus applied and suggest that GSNOR could be a responsive gene downstream of Nrf2 activation.